2021
DOI: 10.1097/brs.0000000000003955
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preoperative Difference in Lumbar Lordosis Between the Standing and Supine Positions on Clinical Outcomes After Single-level Transforaminal Lumbar Interbody Fusion

Abstract: Study Design. Retrospective cohort study.Objective. The aim of this study was to investigate whether a preoperative difference in lumbar lordosis (D-LL) between the standing and supine positions is associated with clinical outcomes after transforaminal lumbar interbody fusion (TLIF). Summary of Background Data. Several factors have been reported to be associated with surgical outcomes after TLIF. However, the association between preoperative D-LL and clinical outcomes after TLIF is unknown. Methods. We enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Therefore, the mean L1S, LL, and SS values reported for this group were very close to that of healthy subjects and can be accepted as an asymptomatic group. On the other hand, we thought that evaluation of spinopelvic parameters in supine position strengthened our study, because the importance of supine imaging tools has been increasing for several reasons [ 26 28 ]. First, the correlation between the spinopelvic parameters are strongest in the supine position and lumbosacral sagittal alingment in the supine position is appromixately equal to that in the prone position which is actually intraoperative position, so supine images can be helpful for the surgical planing [ 26 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the mean L1S, LL, and SS values reported for this group were very close to that of healthy subjects and can be accepted as an asymptomatic group. On the other hand, we thought that evaluation of spinopelvic parameters in supine position strengthened our study, because the importance of supine imaging tools has been increasing for several reasons [ 26 28 ]. First, the correlation between the spinopelvic parameters are strongest in the supine position and lumbosacral sagittal alingment in the supine position is appromixately equal to that in the prone position which is actually intraoperative position, so supine images can be helpful for the surgical planing [ 26 ].…”
Section: Discussionmentioning
confidence: 90%
“…First, the correlation between the spinopelvic parameters are strongest in the supine position and lumbosacral sagittal alingment in the supine position is appromixately equal to that in the prone position which is actually intraoperative position, so supine images can be helpful for the surgical planing [ 26 ]. Second, the difference between LL values measured in supine and standing position was found correlated with postoperative outcome in the patients with adult spinal deformity [ 27 , 28 ]. We believe that supine imaging will be utilized more commonly in the future for the diagnosis and the treatment of spinal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that a higher PI-LL value is associated with worse postoperative clinical outcomes and higher incidence of ASD after lumbar fusion surgery 7 , 9 , 10 . Ohyama et al reported that DiLL is associated with short-term surgical outcomes after TLIF 13 . Moreover, the results of this study revealed that the mid-term clinical outcomes were significantly correlated with DiLL.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies with more patients are warranted to more precisely investigate the incidence of S-ASD between the groups and the influence of a combination of DiLL and PI-LL on the postoperative outcomes. Fourth, there are no background data supporting the appropriateness of classifying patients into DiLL (+) and DiLL (−) groups because DiLL is a newly proposed lumbopelvic parameter 13 . In the future, further studies are needed to clarify the cut-off value for DiLL for classifying patients with normal or abnormal lumbar function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation